Math for the automotive trade - Peterson, John C.; DeKryger, William J. (Boston Cengage Learning, 2018)
The book is hands-on exercises give students the know-how and confidence they need to complete math calculations in the shop by using manufacturer specifications, repair orders, and the professional reference materials included in the book's appendices.
Keywords: Công nghệ kỹ thuật ô tô